When Laws Exist but Certificates Do Not: Can Cross-Ministerial Collaboration Solve Transmigration Land Problems? - Ramli, Asmarani; Nur Heriyanto, Dodik Setiawan; Tamas, Fezer; Latifiani, Dian; Sari, Liani (Faculty of Law, Jambi University, 2025)
The Indonesian transmigration program has many outstanding difficulties. The lack of transmigration land ownership certificates is a big issue. Transmigration land recipients have no land ownership guarantees. The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency and the Ministry of Village, Development of Disadvantaged Regions, and Transmigration collaborate on transmigration land concerns. Using empirical legal research, this study examines the importance of legalizing transmigration land assets. This study fills a gap in existing literature by demonstrating how digital-based cross-ministerial collaboration functions as a legal-institutional mechanism to accelerate transmigration land legalization in Indonesia. This investigation found that 132,949 transmigration land holdings are uncertified. The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) and the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration have unified transmigration land data. The Bhumi-GTRA portal provides spatial and legal information on transmigration land, showcasing the results of this collaboration. This research suggests that the government must immediately address transmigration land issues. Collaborating with relevant ministries on transmigration land will help legalize its assets